The experimental life cycle closure of Andricus truncicolus (Giraud, 1859) (Hymenoptera: Cynipidae: Cynipini) and taxonomic description of its sexual generation - Sottile, Salvatore; Cerasa, Giuliano; Massa, Bruno; Verde, Gabriella Lo (Zootaxa, 2023)
The life cycle of Andricus truncicolus (Giraud, 1869), a species previously known only from its asexual generation, is closed. Laboratory rearing and field sampling have revealed the sexual generation of this species, which develops in a hypertrophic degeneration of the terminal or lateral shoot buds appearing as a muddled agglomerate of leaves on Quercus, section Cerris oaks. We describe for the first time the newly discovered sexual generation of A. truncicolus and provide illustrations and diagnosis for adults and galls of both generations, further observations on biology and information on the species distribution.